Determining potential planting areas in urban regions - Varol, Tuğrul; Gormus, Sevgi; Cengiz, Serhat; Özel, Halil Barış; Cetin, Mehmet (Springer Science and Business Media LLC, 2019)
Impermeable surfaces are getting larger in Turkey, as they are in most parts of the world as urban sprawl increases. The increase in impermeable surfaces leads to air pollution, floods, and overflows due to changes in urban landscapes and ecosystems. In order to prevent such damages, impermeable surfaces must be reduced by the means of urban afforestation. The main purpose of this study is to determine which areas are suitable for urban afforestation, and thus to improve the ecological conditions of the city. Accordingly, the study adopts a method that takes urban density into account. Satellite image classification, canopy measurement and determination of potential afforestation areas have been performed within the boundaries of Bartın Municipality. The IKONOS satellite images have been taken as a base for the study, which has been carried out via ENVI, GIS, and SPSS techniques and Tree Canopy Cover. By excluding the too-small spaces within the study area, as well as the ones too close to infrastructural facilities, I have been able to identify potential planting areas using GIS-based decision-making mechanisms. The existing trees and other plant covers have been noted in order to plan the potential plant cover.Considering the locational suitability of the planting areas and the canopy of the trees, the planting areas have been set out using three grid types: 15 × 15 m (large tree), 10 × 10 m (medium tree), and 5 × 5 m (small tree). A total of 29,773 potential trees have been planned for. After corrections, the potential canopy cover has been calculated to be 0.71 km2. Of the potential trees, 93.34% are small, 5.23% are medium, and 1.43% are large trees. If the potential planting areas determined in this study are forested as calculated, the canopy in Bartın city will increase by approximately 2%. In the city, where impermeable surface areas have expanded because of rapid urban sprawl, this new increase will make an important contribution to the improvement of the city's ecosystem.
Keywords: Conservation of Natural Resources; Ecology; Turkey; Urbanization; Urban Forest; Potential Planting Area; Management, Monitoring, Policy and Law; Forests; Gis; Trees; Remote Sensing; Tree Canopy Cover; Urban Planting; Air Pollution; Cities; Ecosystem; Environmental Monitoring; 15. Life on land; 13. Climate action; 11. Sustainability